Immigration, local institutions and socio-spatial conflicts: The case of the Lo Hermida district in Peñalolén - Palma, Pedro (2019)
The location of immigrants in Santiago has spread from central and peri-central areas towards the periphery neglected and stigmatized, generating new disputes and territorial margins due to ambivalent institutional discourses of inclusion / exclusion and competition for scarce public benefits. Under 'new racism', traditional spaces of exclusion show new nuances of marginality, such as the Lo Hermida district in Peñalolén. Based on a case study, there is an analysis of the action and inaction of local institutions in the construction of socio-spatial conflicts between immigrants and the native population. There are problems of relegation in benefits, exclusive access to housing, and informal work, which denotes a hyper-precarization of immigration and a racialized geography of the conflict.